742 Conventional Surgery vs Endovascular Abdominal Aortic Aneurysm Repair in the Management of Mycotic Abdominal Aortic Aneurysms. (4th May 2021) - Premnath, S; Zaver, V; Kuhan, G; Rowlands, T; Quarmby, J; Singh, S
Abstract: Introduction: This study aimed to look into the short and long-term outcomes in Mycotic Abdominal Aortic Aneurysms (MAAA) managed by Conventional Surgery (CS) and Endovascular Abdominal Aortic Aneurysm Repair (EVAR) Method: Data of 17 patients who underwent CS or EVAR for MAAA from 2001 to 2017 in a single centre were collected. Complications and mortality at 3 years post-procedure were also analysed. Results: Mean age was 66 (54 - 82 years), 15 (88.2%) were males. Mean aortic anterior-posterior diameter was 5.8cm (2.1 – 9.0 cm). 10 patients (58.8%) presented with rupture. 6 (35%) patients demonstrated positive cultures. 4 patients (23.5%) underwent CS and 13 (76.5) had EVAR of which 4 were surgeon modified EVARs. 5 (29%) patients developed complication within 30 days. 4 patients (23.5%) developed graft infection in long term. Total mortality was 5 (29.4%) of which one patient died within 30 days and two within 3 years of procedure. Long-term mortality was found to be significantly higher in patients treated with CS compared to EVAR (p-value 0.022). Conclusions: CS for MAAA has a high mortality rate compared to EVAR. EVAR might be a simple and good alternative for this critical condition in centres with adequate expertise.